2010
DOI: 10.3844/ojbsci.2010.50.53
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic Effects of Dietary Intake of Ripe and Unripe Lycopersicon esculentum (Tomatoes) on Streptozotocin-Induced Diabetes Mellitus in Rats

Abstract: Ripe and unripe tomatoes have been implicated in prevention of chronic diseases such as cancer probably due to their antioxidant, antibiotic, antifungal and anti-inflammatory properties. Problem statement: This study was designed to investigate whether ripe and unripe tomatoes will have hypoglycaemic effect in a chronic disease such as diabetes mellitus that has been characterized with hyperglycaemia. Approach: Twenty albino Wistar rats were divided into 4 groups (2 control and 2 test groups) of 5 rats each. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The latter was accompanied by a decrease in glycogen levels in the livers [14]. Another study reported that feeding unripe tomato to the rats significantly reduced blood glucose level compared to the ripe tomatoes, probably due to the presence of large of amount of glycoalkaloids such as tomatine, dehydrotomatine, and tomatidine [139]. On the other hand, it has been reported that a green tomatorich diet can contribute to cholesterol reduction due to the formation of a complex between α-tomatine and cholesterol [51].…”
Section: Other Biological Activitiesmentioning
confidence: 97%
“…The latter was accompanied by a decrease in glycogen levels in the livers [14]. Another study reported that feeding unripe tomato to the rats significantly reduced blood glucose level compared to the ripe tomatoes, probably due to the presence of large of amount of glycoalkaloids such as tomatine, dehydrotomatine, and tomatidine [139]. On the other hand, it has been reported that a green tomatorich diet can contribute to cholesterol reduction due to the formation of a complex between α-tomatine and cholesterol [51].…”
Section: Other Biological Activitiesmentioning
confidence: 97%
“…Diabetes mellitus (DM) is a syndrome characterized by chronic hyperglycemia and disturbances of carbohydrate, lipid and protein metabolism associated with absolute or relative deficiency in insulin secretion and/or action (Akinnuga et al, 2010). Concern regarding this chronic disease is focused on serious DM-related complications which can affect multiple vital organ systems, thereby leading to more severe and irreversible pathological conditions such as nephropathy, retinopathy, vasculopathy, neuropathy and cardiovascular diseases, as well as hepatopathy (Reid, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a syndrome characterized by chronic hyperglycaemia and disturbances of carbohydrate, fat and protein metabolism associated with absolute or relative deficiency in insulin secretion and/or action (Akinnuga et al, 2010). Chronic elevation of blood glucose eventually leads to long-term complications of diabetes, that leads to various tissue and organs damage that considered major causes of morbidity and mortality in human populations (Lyra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%